2013
DOI: 10.1523/jneurosci.4874-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Reduces Tic-Related Neural Activity via Temporal Locking with Stimulus Pulses

Abstract: A neurosurgical intervention that has shown potential for treating basal ganglia (BG) mediated motor tics involves high-frequency deep brain stimulation (HF-DBS) targeted to the output nucleus of the BG: the globus pallidus internus (GPi). This study used a nonhuman primate (Macaca fuscata) model of BG-meditated motor tics, and investigated the short-term neuronal mechanism that might underlie the beneficial effects of GPi-HF-DBS. In parallel with behavioral tic expressions, phasic alterations of neuronal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…This has been reported also in human and non-human studies (McCairn et al, 2013a). Although the DBS effect ipsilaterally was not recorded, due to the excessive electrical artefact of DBS, it may be inferred from the observed inhibition of the contralateral thalamic activity, that ipsilaterally to the applied DBS side an inhibition of thalamic alpha activity may have occurred at least as strong as on the contralateral side of stimulation.…”
Section: Effect Of Dbssupporting
confidence: 51%
“…This has been reported also in human and non-human studies (McCairn et al, 2013a). Although the DBS effect ipsilaterally was not recorded, due to the excessive electrical artefact of DBS, it may be inferred from the observed inhibition of the contralateral thalamic activity, that ipsilaterally to the applied DBS side an inhibition of thalamic alpha activity may have occurred at least as strong as on the contralateral side of stimulation.…”
Section: Effect Of Dbssupporting
confidence: 51%
“…Our artifact subtraction method makes it possible to identify short-latency responses (0 -3 ms) in close spatial proximity to the stimulating electrode (McCairn and Turner 2009;McCairn et al 2013). Using this technique, we found only one M1 cell (out of 132 cells studied) that responded at a short fixed latency as would be expected of antidromic driving.…”
Section: Discussionmentioning
confidence: 92%
“…The striatal disinhibition model has been applied in multiple studies in both rodents [33][34][35][36] and non human primates. [37][38][39][40][41] Multiple studies that have revealed finely timed tic-related changes in neuronal activity throughout the CBG circuit, including the striatum, cortex, thalamus, GPe, GPi, and SNr. 37,38,[42][43][44] Whereas each of the areas displayed tic-related modulations in neuronal activity in short (subsecond) time scales around tic onset, the modulation type differed substantially (Fig.…”
Section: Tics and Tic-related Neuronal Activitymentioning
confidence: 99%